The Application and Outcome Evaluation of a Social Marketing Intervention to Increase Seasonal Influenza Vaccination among University Students - Daisy Lee; Sharyn Rundle-Thiele; Ben Y. F. Fong; Gabriel Li (Vaccines, 2022)
Seasonal flu vaccination rates among university students are exceedingly low and research focused on voluntarily influencing vaccination uptake is limited. This study outlines the development, implementation, and evaluation of a theory-driven social marketing vaccination intervention following the co-create-build-engage (CBE) framework. This study drew upon a pre-intervention segmentation study and co-created interventions targeted at receptive segments. The intervention delivered a significant 343% increase in vaccination rates using a difference-in-difference analysis. Online communication channels effectively engaged students to register for and receive their flu vaccine Almost 90% of students who received vaccinations signed up in the first two weeks of the intervention program indicating that those who can be motivated will act early in the flu season. Financial incentives, as found in previous studies, were confirmed as highly effective in increasing awareness and influencing vaccination uptake behaviours. Friend referral incentives were also found to be influential in motivating vaccination uptake. Suggestions are provided for future research and practical implementation of interventions on university campuses to motivate flu vaccination and other health behaviours.